Clinical algorithm for direct restoration of class II cavities - Andreea Ciurea; Iulia Cristina Micu; Alexandra Roman; Daniela Condor; Andrada Soancă (Amaltea Medical Publishing House, 2019)
Direct dental restorations are probably the most common procedures performed daily by the practitioners, and the alert rhythm with which restorative materials appear on the dental market, makes it difficult to choose a material that will ensure the clinical success. Direct class II restorations can sometimes be a real challenge, in terms of choosing the right matrix system, the restorative material and its application. Thus, the purpose of this article is to provide for the practitioners, two different restoration techniques with two ormocer type materials.